Preparation and Characterization of Bio-Oil Modified Urea-Formaldehyde Wood Adhesives - Ben Li; Ji-Zong Zhang; Xue-Yong Ren; Jian-min Chang; Jin-sheng Gou (BioResources, 2014)
Wood-derived bio-oil was used to decrease formaldehyde emissions from urea-formaldehyde (UF) resin during the process of making three-layered plywood. The obtained bio-oil urea formaldehyde (BUF) resins were characterized by their physical, chemical, and mechanical properties (e.g., viscosity, solid content, pH value, shelf life, formaldehyde emissions, and bonding strength), analyzed for their specifications, and characterized with Fourier transform infrared spectroscopy and thermogravimetric analysis. The synthesized resins were further employed to prepare the plywood with the veneers glued. The resulting BUF plywood displayed much lower formaldehyde emissions and comparable bonding strength. For the modification on formaldehyde emission of the plywood, it was concluded that the bio-oil can be used to effectively reduce formaldehyde emissions from UF wood adhesive.